martes, 4 de septiembre de 2012

1) (- 2 - 3 + 4 ) . 5 - 9  . ( - 2 - 6 ) =  - 1 . 5 - 9 . ( - 8 ) =    - 5 - 9 .( - 8 ) =   - 5 + 72 = +67

2) ( - 5 - 10 - 32 ) . ( 4 -8 - 16 ) =   - 47 . ( - 20 ) = + 940  

3)  - 2 + 3 . 5 - 7 . ( - 3 + 2 - 8 ) - 4 =   - 2 + 3 . 5 - 7 . ( - 9 ) - 4 =  - 2 + 3 . 5 + 63 - 4 =   - 2 + 15 + 63 - 4 =      ( 63 + 15 ) - ( 4 + 2 ) =    78 - 6 =   +72  


4) ( 2 - 10 ) . ( 6 - 3 ) - ( - 8 - 2 ) . ( - 9 - 7 ) =  - 8 . 3 - ( + 8 + 2 ) . ( - 16 ) =  -  24 - ( 10 ) . ( 16 ) =   - 24 - 160 = -184


5)  15 + 16 . 2 - 3 . ( 5 . 2 + 4 - 3 . 2 ) - [ 2 + 2 . ( - 2 ) - 9 ] . ( - 5 ) =  15 + 16 . 2 - 3 . ( 10 + 4 - 6 ) - [ 2 - 4 - 9 ] . ( - 5 ) =15 + 16 . 2 - 3 . 8 - [ 2 - 4 - 9 ] . (  - 5 ) = 15 + 16 . 2 - 24 -  [ 2 - 4 - 9 ] . (  - 5 ) = 15 + 16 . 2 - 24 - 2 + 4 + 9 . ( - 5 ) =15 + 32 - 24 - 2 + 4 - 45 = ( 15 + 32 + 4 ) - ( 24 + 2 + 45 ) =51 - 71 = -20

No hay comentarios:

Publicar un comentario